Enumeration of the Edge Weights of Symmetrically Designed Graphs. (9th September 2021) - Javaid, Muhammad; Afzal, Hafiz Usman; Bonyah, Ebenezer
Abstract : The idea of super a, 0 -edge-antimagic labeling of graphs had been introduced by Enomoto et al. in the late nineties. This article addresses super a, 0 -edge-antimagic labeling of a biparametric family of pancyclic graphs. We also present the aforesaid labeling on the disjoint union of graphs comprising upon copies of C 4 and different trees. Several problems shall also be addressed in this article.